Virtual Reality in Libraries: Does VR create a Safer Space for 2SLGTBQ+ and IBPOC people? - Tanaka, Candie (Pathfinder: A Canadian Journal for Information Science Students and Early Career Professionals, 2023)
Research Question: Can Virtual Reality (VR) Create a Fourth Space in Libraries that is a safer space for 2SLGTBQ+ and IBPOC people? Libraries are considered third places between work and home, if there is access to VR could that create a fourth space for individuals with intersectional identities to explore in library settings?